Dietary Behaviors and Portion Sizes of Black Women Who Enrolled in SisterTalk and Variation by Demographic Characteristics - Gans, K.M.; Risica, P.M.; Kirtania, U.; Jennings, A.; Strolla, L.O.; Steiner-Asiedu, M.; Hardy, N.; Lasater, T.M. (Journal of Nutrition Education and Behavior, 2009)
Objective: To describe the dietary behaviors of black women who enrolled in the SisterTalk weight control study. Design: Baseline data collected via telephone survey and in-person screening. Setting: Boston, Massachusetts and surrounding areas. Participants: 461 black women completed the baseline assessments. Main Outcome Measures: Measured height and weight; self-reported demographics, risk factors, and dietary variables including fat-related eating behaviors, food portion size, and fruit, vegetable, and beverage intake. Analysis: Analysis of variance (ANOVA) models with food habits questionnaire (FHQ) scores as the dependent variable and demographic categories as the independent variables; ANOVA models with individual FHQ item scores as the dependent variable and ethnic identification as the independent variable. Results: More than 60% reported eating < 5 servings of fruits and vegetables/day. Self-reported portion sizes were large for most food items. Older age, being born outside the United States, living without children, and being retired were significantly associated with a higher prevalence of fat-lowering behaviors. The frequency of specific fat-lowering behaviors and portion size also differed by ethnic identification. Conclusions and Implications: The findings support the need for culturally appropriate interventions to improve the dietary intake of black Americans. Further studies should examine the dietary habits, food preparation methods, and portion sizes of diverse groups of black women. © 2009 Society for Nutrition Education.
Keywords: African American; Black; Dietary habits; Eating habits; Fat; Fruit and vegetable; Portion size; Women